Carbon monoxide exposure in youth ice hockey - Macnow, T.; Mannix, R.; Meehan, W. P. (Clinical Journal of Sport Medicine, 2017)
Objective: To examine the effect of ice resurfacer type on carboxyhemoglobin levels in youth hockey players. We hypothesized that players in arenas with electric resurfacers would have normal, stable carboxyhemoglobin levels during games, whereas those in arenas with internal combustion engine (IC) resurfacers would have an increase in carboxyhemoglobin levels.